Determination of physicochemical properties of formulated fish feed supplemented with microalgae from bioremediation process - A. Talip, Balkis; Neo, Zhi Zing; Hairuddin, Nur Diyana; Radin Mohamed, Radin Maya Saphira; Muhammad, Norhayati; Basri, Hatijah; Abdullah, Norazlin; Mohamad Kahar, Ernna Erynna; Al-Gheethi, Adel Ali Saeed; Abdullah, Shakila (Penerbit Universiti Teknologi Malaysia Press, 2019)
This study was conducted to determine the potential of Scenedesmus sp. from phycoremediation as fishmeal replacer in formulated fish feed targeted for Oreochromis niloticus. Formulated fish feeds were designated with Formulation 1 being the control; in Formulation 2 and 3, 2 % of fishmeal was substituted with Scenedesmus sp. cultivated in Bold’s Basal Medium, and in artificial wastewater, respectively. It was found that supplementation with Scenedesmus sp. did not alter the hardness of the feed pellets (p>0.5), but the water stability of Formulation 2 and 3 was significantly lower than Formulation 1 (p<0.05). Zero correlation was established based on the fishmeal content with water stability (p>0.05). Negative correlation was determined between moisture content and water stability of Formulation 2 and 3 (p<0.05). This study showed the phycoremediation ability of Scenedesmus sp. in artificial wastewater with removal efficiency of 12.42 % and 49.25 % for Zn and Fe, respectively. It also found that biomass productivity of microalgae was lower in artificial wastewater compared to that in Bold’s Basal Medium. Overall, the results of the study suggested the sustainability of wastewater-treated microalgae as fishmeal replacer had little effect on physicochemical properties of fish feed.